Effect of hydrofluoric acid concentration and etching time on the adhesive and mechanical behavior of glass-ceramics: A systematic review and meta-analysis - Riesgo, Bibiana Vogel Peres; Rodrigues, Camila da Silva [UNESP]; Nascimento, Luiza Pereira do; May, Liliana Gressler (Elsevier, 2023)
Statement of problem: The process prior to cementing a glass ceramic requires that the surface be etched with hydrofluoric acid in order to improve its adhesion. HF acid concentration and conditioning time can influence the shape and size of the micro retentions created on the ceramic surface, and consequently both reflect on the bond strength to the cementing agent and on the mechanical behavior of the material. Purpose: This study systematically reviewed the literature to compare the effect of alternative vs. manufacturer-recommended hydrofluoric (HF) acid etching time and concentrations on the adhesive and mechanical behavior of feldspathic (FEL), leucite-reinforced (LEU), lithium disilicate (LD), and lithium silicate (LS) glass-ceramics. Material and methods: Searches were performed in the PubMed/Medline, Scopus, LILACS, and Web of Science databases. The search strategy was independently carried out in two steps (title and abstract reading, and full-text reading) by two reviewers. The in vitro studies had to include at least one manufacturer-recommended protocol group (comparison) and one alternative HF acid concentration or etching time (intervention). Meta-analyses were carried out separately for each ceramic (FEL/LEU or LD/LS), outcome (bond or flexural strength), test condition (baseline or after aging), and analyzed factor (HF acid etching time or concentration). Results: A total of 86 from 3375 relevant studies were selected for full-text analysis, 28 were included for qualitative synthesis, from which 20 were used in the meta-analysis. Baseline and aging meta-analyses for bond strength of FEL/LEU showed no significant effect of HF concentration and no significant effect of HF etching time (at baseline). Meta-analyses showed that <5%HF acid (20s) and etching for more than 20 s (5% or 10%HF acid) decreases the baseline bond strength of LD/LS. No significant difference was observed after aging. In addition, HF acid etching with concentrations above 5% (20s) or for more than 20 s (5%HF acid) reduces the flexural strength of LD/LS. Conclusions: The manufacturer-recommended protocol of hydrofluoric acid etching (5% for 20 s) is the most efficient regarding bond and flexural strength of LD/LS. HF acid etching time and concentration do not seem to affect the bond strength of FEL/LEU, but there is a lack of studies on the effect of etching protocols on their mechanical behavior.
Keywords: Ceramic. surface treatment. adhesion. fatigue. strength